The Spirit of Da'wah Nafsiyah in the Corporate Work Culture of PT. Telkom Tbk - Mujib, Abdul; Enjang, Enjang (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aims to analyze the values of spirituality in the company's work culture. Where the researcher directs the effort to explore work culture as a da'wah spirit in the context of nafsiah. The research was conducted using an interpretive paradigm and a qualitative approach. Case studies are a research method that bridges concrete observations and abstract meanings using interpretive techniques. The interpretive process used in this type is to adopt a different way from quantitative, namely by using various theories to analyze cases. Data were collected through observation, interview, and documentation techniques. The results showed that there are three main pillars of the work culture of PT. Telkom Tbk, namely always the best, the leadership architecture, and the Telkom way. All three show the values of spirituality in strengthening employee work culture. Implementing the three work cultures gave rise to Spiritual Capital Management, which became the spirit of nafsiah da'wah in maintaining character at the individual, inter-individual and institutional levels.